Security, environment and development in Zone 3 of International Conference on the Great Lakes Region: A case study on an integrated approach to sustainable peace in borderlands - Isabell Kempf; Nathan Mwesigye Byamukama; Stephen Mwachofi Singo (United Nations Research Institute for Social Development (UNRISD), 2022)
This study examines and provides reasons for the stalled implementation of an integrated approach to addressing security, environment and development challenges in Zone 3 of the International Conference on the Great Lakes Region (ICGLR). Zone 3, which covers the borderlands connecting Uganda, Kenya and South Sudan, is characterized by the proliferation of illicit small arms and light weapons, cattle rustling, and persistent cross-border inter-communal conflicts and human rights violations. The zone experiences extreme climatic conditions ranging from prolonged drought and environmental destruction to frequent related food shortages and famine. It is an area with rugged terrain, with little or no infrastructure: good roads, electricity and water are scarce. The area suffers from years of marginalization and high poverty levels, with very little government presence owing to its remote location and distance from state capitals. In 2006, regional member states signed a treaty that established a regional organization, the ICGLR, together with its integral protocols and programs of action-all binding on member states and designed to effectively address threats to security, environment and development in Zone 3. However, the implementation of these instruments has been disappointing. Countries of Zone 3 preferred standalone, piecemeal, national initiatives focused on state security over holistic human security issues across these borderlands. Consequently, militarism and forced disarmament without effective stakeholder participation delivered no meaningful outcomes to people's security. The study concludes that a paradigm shift towards a collaborative, regional multisectoral and holistic integrated approach is required to tackle both Zone 3's combined persistent problems and widespread underdevelopment and poverty, as well as the general lack of concerted joint action by the three governments. It provides policy recommendations for designing and implementing integrated approach-based projects within Zone 3 and in the surrounding regions beyond.
Keywords: 330